Efetivação do trabalho decente nas relações de trabalho - Pinheiro, Felipe Fernandes (2021)
This study aimed to analyze decent work and its effectiveness in labor relations not subject to an employment relationship. The analysis started from the premise that decent work means equal opportunities for everyone to get work that is productive and delivers a fair income, security in the workplace and social security, freedom to express their concerns and participate in the decisions that affect their lives and fair conditions of dignity. To achieve the study’s objective, the dissertation began with the review of human work redefinition in Western culture, in order to find the foundations of its appreciation as a dignifying activity and the reasons that justify the establishment of a global concept of decent work. The study also analyzed the historical background that led to the creation of the concept, its four strategic pillars - promotion of fundamental rights at work, employment generation, social protection and strengthening of social dialogue - and narrowed it, based on a solid bibliographic study which revealed the scope of each of its requirements. From this on, it was possible to verify that the ILO does not understand employment in the same way as it is treated in the Brazilian legal system. That conclusion makes it possible to glimpse decent work beyond employment and, from that, ensure a professional status full of safety and dignity for all workers. From this finding, the next step was to confront each of the requirements demanded by decent work with the Brazilian constitutional norms and it revealed the axiological alignment between the Federal Constitution and the ILO's concept of decent work. After all, in the Brazilian constitutional typology, all the requirements demanded by the ILO are considered either fundamental rights or foundations and objectives of the Republic, therefore, they are guaranteed to all human beings, thus, are secured to all workers. Since the Constitution ensures the rights required by decent work to workers not subject to an employment relationship, it is concluded that decent work can be effectuated to all workers, including those who are not subject to employment relationships.